(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Methods for learning English are varied, and one of them is cartoon. When choosing the right cartoon for a specific audience, it not only helps improve language skills, but also allows you to get acquainted with the correct pronunciation. A correctly selected cartoon, taking into account the interests and level of language training, does not cause difficulties in understanding. In the process of watching developed, such important skills as language intuition and the ability to predict the content.